Visual Identity and Digital Marketing of Loka Pere Banana Bioproducts to Empower Adolang Village Creative Economy - Mufti Hatur Rahmah; Wulan Ayuandiani; Muhammad Irfan; Aisyah Aisyah; Muh Irham Risaldi; Erwin Erwin; Muhammad Yusuf; Nurhaliza Nurhaliza; P Cici (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2026)
The community service program in Adolang Village, Majene Regency, optimizes the potential of Loka Pere banana as an endemic functional commodity by diversifying products, implementing laboratory-based quality standards, and developing digital marketing. Key interventions include product innovation (Mini Sambusa and Dodol using palm caramel and pandan leaves), proximate-based nutritional standardization, strengthening visual identity, and digital marketing training. Laboratory analysis confirms that the Loka Pere banana is rich in dietary fiber and maintains a stable macronutrient composition, supporting its functional food potential. Evaluation from 33 participants showed very high acceptance (100% positive responses). The program successfully improved product quality, consumer trust, and digital branding capacity, transforming local foods into standardized, competitive functional products. Future efforts should focus on business licensing (NIB, Halal, PIRT) and the cultivation of sustainable raw materials to ensure supply continuity. Contribution to Sustainable Development Goals (SDGs):SDG 2: Zero HungerSDG 8: Decent Work and Economic GrowthSDG 12: Responsible Consumption and ProductionSDG 13: Climate Action SDG 17 : Partnerships for the Goals